2003
DOI: 10.1080/1475636031000152286
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Jack Bean Urease by Allicin

Abstract: Allicin--diallyl thiosulfinate--is the main biologically active component of freshly crushed garlic. Allicin was synthesized as described elsewhere and was tested for its inhibitory ability against jack bean urease in 20 mM phosphate buffer, pH 7.0 at 22 degrees C. The results indicate that allicin is an enzymatic inactivator. The loss of urease activity was irreversible, time- and concentration dependent and the kinetics of the inactivation was biphasic; each phase, obeyed pseudo-first-order kinetics. The rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Therefore, SH‐blocking reagent was employed to examine its effects on the inhibitory activity of PA against ureases. When DTT was added to the pre‐incubation medium, instead restoring the inhibition of urease activity by some reported compounds like allicin, quinine, and flavonoid (Juszkiewicz et al ., ; Kot, ; Tan et al ., ), the inhibitory activity of PA was strengthened by DTT. Chemical studies have shown that various sesquiterpenes react with thiols (Kupchan et al ., ; Kupchan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SH‐blocking reagent was employed to examine its effects on the inhibitory activity of PA against ureases. When DTT was added to the pre‐incubation medium, instead restoring the inhibition of urease activity by some reported compounds like allicin, quinine, and flavonoid (Juszkiewicz et al ., ; Kot, ; Tan et al ., ), the inhibitory activity of PA was strengthened by DTT. Chemical studies have shown that various sesquiterpenes react with thiols (Kupchan et al ., ; Kupchan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of urease inhibition by garlic have been already published (Juszkiewicz et al, 2003(Juszkiewicz et al, , 2004Zaborska et al, 2009). Thiosulfinates of garlic extracts inactivate urease as a result of a modification of urease -SH groups.…”
Section: The Mechanism Of Urease Inhibitionmentioning
confidence: 98%
“…The Brassica species contain only methiin, which is converted into methylmethanethiosulfinate and then to dimethylthiosulfonate, dimethylsulfide and polymethylsulfides (Kyung & Lee, 2001;Rose et al, 2005). The inhibition of jack bean urease by garlic extract has already been investigated by our staff (Juszkiewicz, Zaborska, Sepioł, Góra, & Zaborska, 2003;Juszkiewicz, Zaborska, Łaptaś, & Olech, 2004;Zaborska, Karcz, Kot, & Juszkiewicz, 2009). It has been found that allicin the most abundant TS present in fresh garlic extract is responsible for inhibition of the enzyme.…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, this compound formed a very strong hydrogen bond interaction with the Cys592 in the mobile flap closing the active site of the urease enzyme [54] with bond distance 2.12 Å (Figure 7). In summary, based on this analysis, all synthesized compounds interacted with the catalytic functional sites of the target proteins.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%